2015
DOI: 10.1186/s13049-015-0131-1
|View full text |Cite
|
Sign up to set email alerts
|

Physicians using ultrasound in Danish emergency departments are mostly summoned specialists

Abstract: BackgroundEmergency ultrasound is a relatively new diagnostic discipline. It is used as an extension of the clinical examination and is ideal in the setting of acute illness. The objective of this study was to investigate how many Emergency Departments (EDs) in Denmark have implemented emergency ultrasound. We also wanted to give an idea of how many and which physicians have adopted ultrasound as a diagnostic tool so far.MethodsThe study was a cross-sectional, descriptive, multicenter survey that included all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…In this study however, we found that male physicians used ultrasound more than their female colleagues. Other studies have also shown this, suggesting that male physicians are more likely to be early adopters of ultrasound [9,17]. Noteworthy, one study found that females felt they required more training compared to males to start using POCUS [18].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study however, we found that male physicians used ultrasound more than their female colleagues. Other studies have also shown this, suggesting that male physicians are more likely to be early adopters of ultrasound [9,17]. Noteworthy, one study found that females felt they required more training compared to males to start using POCUS [18].…”
Section: Discussionmentioning
confidence: 88%
“…Emergency departments from other countries have reported much higher rates of ultrasound availability [9,10], albeit not directly comparable due to the structural organization of emergency health care in Norway with smaller volume clinics staffed by general practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Critical care ultrasonography (CCUS) is a deliberately focused examination, aimed at rapidly answering straightforward clinical questions [1]. In the field of emergency and critical care medicine, CCUS is increasingly used to guide interventions in critically ill patients in various settings by experts and novices [2][3][4][5][6][7][8][9][10][11][12][13][14]. The training process required for users to attain competency in CCUS has varied widely between studies, reflecting the diversity in CCUS training between centers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is variability among statements from stakeholders regarding the type of training, the required number of hours spent and examinations performed by the trainee to achieve competency in CCUS [15][16][17]. However, besides these disparities, individual physicians struggle with barriers to its use, such as perceived difficulty in obtaining adequate technical skills [13], limitations in training, need (perceived and real), and costs [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…One might argue that the inclusion period could be extended further back in time. In recent years, however, the treatment possibilities have expanded within the prehospital medical services [ 36 , 37 ], alongside improved diagnostic capabilities through point of care ultrasound and arterial blood gas analysis [ 38 ]. Therefore, the authors believe that the possible adjustments to create a larger sample size would result in a more heterogeneous patient population.…”
Section: Discussionmentioning
confidence: 99%